Organização de partituras: uma proposta a partir do estudo de caso da Banda Filarmônica Cardeal Leme - Oliveira, Marcella Bortoni de (Universidade Federal de São Carlos, 2025)
This thesis aims to propose a manual for the organization of music scores designed to facilitate and expedite the retrieval of these documents. The research originates from the observed lack of accessible and systematized methods for the processing and retrieval of published music. This deficiency compromises the access, use, and preservation of these documents, thereby directly impacting their primary users: musicians. Methodologically, this is an applied research study with exploratory objectives, employing a qualitative approach and a descriptive character. It is structured in three stages: a literature review, a case study, and the development of a practical proposal. The literature review covered the origin and definition of music scores, the organization of collections within information units, and the specific characteristics of musical documents. The case study was conducted with the Cardeal Leme Philharmonic Band (Banda Filarmônica Cardeal Leme), located in Espírito Santo do Pinhal, São Paulo state. This study allowed for a diagnosis of the collection's physical condition and an understanding of the historical importance of the scores to the institution. Based on this analysis, a methodological proposal for organization was developed, structured in ten stages ranging from the acquisition and sorting of documents to circulation control. The proposal details technical procedures for cleaning, housing, cataloging, labeling, and physical arrangement, based on library best practices. The study indicates that the application of the proposed methodology provides standardization, greater efficiency in information retrieval, and the proper preservation of the collection, thereby extending and expanding its use. Furthermore, the developed model is adaptable and can serve as a reference for other bands, music schools, and similar archives. It is concluded that the systematic organization of music scores contributes to the valorization of the cultural and historical heritage of institutions, strengthening their institutional memory and expanding the role of the librarian in the management of special collections.
Organisation of musical scores: a proposal based on the case study of the Cardeal Leme Philharmonic Band
Keywords: Organização da informação; Documentos musicais; Partituras; Ciência da Informação; Information organization; Musical documents; Music scores; Information Science; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA; 4. Educação de Qualidade; 9. Indústria, Inovação e Infraestrutura; 11. Cidades e Comunidades Sustentáveis; 16. Paz, Justiça e Instituições Eficazes